959. BREXIA MADAGASCARIENSIS: Celastraceae. (5th November 2020) - Corcoran, Marcella; Dequiret, Solène; Pickering, Thomas E.M.; Cable, Stuart
Summary: Brexia madagascariensis (Lam.) Ker Gawl is native in East Madagascar. There are at least 25 known subpopulations growing mostly in humid forest (IUCN 2020), particularly in remnant patches of coastal forest. It was listed as 'Least Concern' on the IUCN Red Lists in 2007; however, continuing pressure on forests and potential taxonomic changes may require this to be reviewed. Madagascar has very high deforestation rates, primarily caused by logging and widespread shifting cultivation. Germination and cultivation for in‐situ and ex‐situ conservation are easily achievable and this small tree is ideal for education and display in botanic gardens. The leaves of juvenile plants are long and spiny, while the adult leaves tend to be more rounded and lack the spines.